2022
DOI: 10.1111/ejn.15563
|View full text |Cite
|
Sign up to set email alerts
|

Modulating verbal working memory with fronto‐parietal transcranial electric stimulation at theta frequency: Does it work?

Abstract: Oscillatory theta activity in a fronto‐parietal network has been associated with working memory (WM) processes and may be directly related to WM performance. In their seminal study, Polanía et al. (2012) (de‐)coupled a fronto‐parietal theta‐network by applying transcranial alternating current stimulation (tACS), and showed that anti‐phase tACS led to slower and in‐phase tACS to faster response times in a verbal WM task compared to placebo stimulation. In the literature, this ‘synchronization‐desynchronization’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
4
14
0
Order By: Relevance
“…Overall, accordance to with several previous studies ( Vosskuhl et al, 2015 ; Pahor and Jaušovec, 2018 ; Abellaneda-Pérez et al, 2020 ; Biel et al, 2021 ), our findings indicated that theta band activity was strongly associated with verbal working memory, and that theta tACS improved verbal working memory performance. Moreover, our study extends these findings, as we investigating the EEG characteristics correspond to the improvements in working memory performance in both HP and LP groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, accordance to with several previous studies ( Vosskuhl et al, 2015 ; Pahor and Jaušovec, 2018 ; Abellaneda-Pérez et al, 2020 ; Biel et al, 2021 ), our findings indicated that theta band activity was strongly associated with verbal working memory, and that theta tACS improved verbal working memory performance. Moreover, our study extends these findings, as we investigating the EEG characteristics correspond to the improvements in working memory performance in both HP and LP groups.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with sham-tACS and transcranial direct current stimulation (tDCS), 40 Hz tACS resulted in increased performance in terms of d prime (an accuracy discriminability index). Biel et al (2021) also recently reported that frontoparietal in-phase and in-phase focal theta tACS substantially improved verbal three-back task performance when compared with placebo stimulation.…”
Section: Introductionmentioning
confidence: 82%
“…Overall, accordance to with several previous studies (Biel et al, 2021;Kilian et al, 2020;Pahor & Jaušovec, 2018;Vosskuhl et al, 2015), our findings indicated that theta band activity was strongly associated with verbal working memory, and that theta tACS improved verbal working memory performance. Moreover, our study extends these findings, as we investigating the EEG characteristics correspond to the improvements in working memory performance in both HP and LP groups.…”
Section: The Modulatory Effects Of 8 Hz (Selected Stimulation) 40 Hz (Control) and Sham Stimulation On Verbal Working Memorysupporting
confidence: 93%
“… Cavaliere et al (2018) also observed that patients have predominant posterior theta activity. Theta activity is generally considered to reflect fundamental cognitive functions ( Biel et al, 2022 ; Cowley et al, 2022 ). An association between increased theta connectivity and cognitive dysfunction has been reported in some diseases such as Alzheimer’s disease, Parkinson’s disease, and schizophrenia ( Andreou et al, 2015 ; Iyer et al, 2020 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%